Dykes on permafrost, Kelsey Generating Station, Manitoba - Johnston, G. H. (1969)
Performance studies of two major, but relatively small (2000- ft (~610 m) long, maximum height 20 ft (6.1 m), sand dykes constructed on perennially frozen ground were initiated in 1958 at the Kelsey Generating Station of Manitoba Hydro on the Nelson River. Permafrost occurred under these dykes in scattered islands or patches of variable thickness and size. Preliminary analyses, though only aproximate, indicated that within a 50-year period significant thawing would occur beneath the dyke-water interface and that the permafrost under the reservoir would thaw completely. Ground settlements of as much as 6 ft (1.8 m) were to be expected as thawing took place. To check the estimated performance, field instrumentation was installed and an observational program begun in 1959. A distinct pattern of thawing and settlement each year has been observed. Major thawing and settlement occur during the summer months at rates that are greater than those experienced during the winter. The change in rate of thaw (and thus also the rate of settlement, which is partly a function of thawing) is directly connected with the change in water temperature or rate of heat flow into the ground. Des études du comportement des deux digues importantes, bien que de dimensions réduites (2,000 pi. de long, 20 pi. de hauteur maximum), construites sur un sol constamment gelé, ont été entreprises en 1958 à la station Kelsey de l'Hydro- Manitoba sur la rivière Nelson. Le permafrost sous les digues se présentait sous forme d'ilots dispersés ou de lentilles de dimensions et d'épaisseur variable. Des études préliminaires, bien que très approximatives, avaient montré qu'un dégel important se produirait dans une période de 50 ans au dessous du contact eau-digue et que le permafrost disparaîtrait complètement sous le réservoir. Des tassements pouvant atteindre 6 pieds devaient être envisagés pendant la période de dégel. Afin de vérifier ces valeurs estimées les ouvrages ont été instrumentés et un programme d' observation a commencé en 1959. Un schéma de dégel et de tassement différent a été observé chaque année. L'essentiel du dégel et du tassement se produit durant les mois d'été à des vitesses supérieures à celles mesurées durant l'hiver. Le changement dans la vitesse de dégel (donc aussi dans la vitesse de tassement, qui est partiellement une fonction du dégel) est directement fonction du changement de température de l'eau, ou du dépôt de chaleur vers le sol. Peer reviewed: No NRC publication: Yes